2012
DOI: 10.1521/ijct.2012.5.3.341
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Model of Social Phobia: Applicability in a Large Adolescent Sample

Abstract: cognitive model of social phobia has been extensively evaluated in adults. However, very little data is available on the applicability to social anxiety in adolescence. This study examines the model's applicability in a large adolescent sample. 581 students (aged 14-20) completed questionnaires assessing social anxiety, depression, and variables of the cognitive model (namely safety behaviors, negative social cognitions and social attitudes, self-focused attention, recurrent self-images, pre-and post-event pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 47 publications
10
57
0
1
Order By: Relevance
“…Supportive evidence for this hypothesis in adolescents is provided by three questionnaire studies. Schreiber et al ( 2012 ) and Hodson et al ( 2008 ) reported on studies undertaken with German (aged 14–20 years) and UK (aged 11–14 years) school samples respectively. In their large non-clinical sample of 581 adolescents and young adults, Schreiber et al ( 2012 ) found that those scoring in the upper quartile of the German version of a measure of social anxiety, the Social Phobia Anxiety Inventory (SPAI; Turner et al ( 1989 )) endorsed more frequent negative social cognitions in social situations (e.g.…”
Section: A Review Of Studies Examining the Applicability Of The Cognimentioning
confidence: 99%
“…Supportive evidence for this hypothesis in adolescents is provided by three questionnaire studies. Schreiber et al ( 2012 ) and Hodson et al ( 2008 ) reported on studies undertaken with German (aged 14–20 years) and UK (aged 11–14 years) school samples respectively. In their large non-clinical sample of 581 adolescents and young adults, Schreiber et al ( 2012 ) found that those scoring in the upper quartile of the German version of a measure of social anxiety, the Social Phobia Anxiety Inventory (SPAI; Turner et al ( 1989 )) endorsed more frequent negative social cognitions in social situations (e.g.…”
Section: A Review Of Studies Examining the Applicability Of The Cognimentioning
confidence: 99%
“…Given the relative paucity of sophisticated cognitive models of childhood anxiety disorders, investigators have begun to examine whether disorder-specific cognitive models that have been developed for adults can also be applied to older children and adolescents. In the field of social anxiety, Clark and Wells' model (1995) has received the most attention so far (Ahrens-Eipper & Hoyer, 2006;Hodson, McManus, Clark, & Doll, 2008;Schreiber, Höfling, Stangier, Bohn, & Steil, 2012;Vassilopoulos, 2008b). Cartwright-Hatton, Reynolds, and Wilson, (2011) recently reviewed the evidence regarding the developmental appropriateness of adult models at different ages and concluded that -at least for older children and adolescents -these models (the Clark & Wells model included) do appear to be "largely applicable."…”
Section: Anticipatory Processing In Childrenmentioning
confidence: 99%
“…Furthermore, it is possible that intrusive negative images are more problematic in adolescence, when individuals are less able to attain cognitive control over mental imagery [9]. Three observational studies have reported on the relationship between social anxiety and negative self-imagery in adolescents and a medium association was reported [10][11][12], for a review see Leigh and Clark [13]. However, all three studies were correlational and cross-sectional and so cannot answer the question of whether negative self-imagery plays a causal role in maintaining adolescent social anxiety.…”
Section: Introductionmentioning
confidence: 99%